Maintenance treatment of diabetic patients, associating arterial obstructive tibio-peroneal disease - Wolosker, Nelson; Rosoky, Ruben Miguel Ayzin; Muraco Neto , Baptista; Langer, Berilo (São Paulo Medical Journal, 1995)
When a melito-diabetic patient presents trophic infected injury on the limb, it is essential an evaluation of the circulatory conditions for therapeutic procedures orientation. In some circumstances, although arterial pulsation is absent, there is no ischemia of tissues. In these cases, the maintenance treatment, with eventual resection of the necrosed and infected tissues may be adopted. Evolution of 70 diabetic patients with trophic injuries on extremities were submitted to a maintenance treatment. Age of patients varied from 28 to 88 years, with an average of 56.8. The most occurrence was verified in women, with 42 cases. Diabetes non-dependant on insuline (type II) was observed in 64 patients (91.5%), being the remaining 6 patients of type I. Diabetic retinopathy was observed in 14 (20%) of the patients, neuropathy in 22 (31%) and nephropathy in 8 patients (11.4%). All the patients presented arterial pulsation until the popliteal region. They were divided in 2 groups, considering trunk arteries of legs: Group I, pervial legs arteries, composed by 48 patients; Group II, occluded legs arteries, with 22 patients. In what refers to the anatomic local of the injuries, patients were classified in three groups: Group A, formed by 32 patients (45.7%), presenting injuries in one or two toes only, without affecting the metatarsic region; Group B, formed by 16 patients (22.9%), trophic injuries affecting the metatarsic region and Group C, formed by 22 patients (31.4%), injuries affecting the calcaneous region. Injuries in both of the groups were caused by mechanical traumatism. Duration of the injury in the inferior member varied from 7 to 48 days, resulting in a 12 days average. Analyzing pervicacity in trunk arterias and evolution of patients, it may be observed that there has been a significantly better result in those with all the pulses present (81.3% x 45.5%)(p<0,01). Studying the injury locals associated to the evaluation of the cases, we may observe that for injuries in the extreme digital, result is significantly better than in locals more nearly. When distal pulses are absent, there is no significant difference in the result of the treatment, being performed in distal injuries or in the more near ones (p>0,05)(Table IV).